Serum neuron-specific enolase, a marker of neuronal injury, increases after catheter ablation of atrial fibrillation. Issue 11 (November 2018) - Acibuca, Aynur; Vurgun, Veysel Kutay; Gerede, Demet Menekse; Altin, Ali Timucin; Gul, Inci Sule; Candemir, Basar; Isikay Togay, Canan; Kilickap, Mustafa; Akyurek, Omer
Objective: Catheter ablation of atrial fibrillation (AF) can lead to thromboembolic complications, especially stroke. We measured the periprocedural serum neuron-specific enolase (NSE) level, which is a biomarker of neuronal injury, after ablation of AF. Methods: Forty-three patients with paroxysmal AF were prospectively enrolled before radiofrequency ablation. A neurological examination was performed before and after the procedure. The serum NSE level was determined before and at the end of the procedure and at 2, 24, and 48 h after the procedure. Results: No patients developed new neurological deficits. However, the median (interquartile range) NSE level increased after ablation from 6.7 (3.87) ng/mL at baseline to 11.48 (5.3) ng/mL at 24 h postoperatively. The NSE level exceed the upper reference limit of normal (17 ng/mL) in 14 patients (33%), and these patients were found to have a larger left atrium. Conclusions: Serum NSE increased in most of the patients undergoing ablation for AF, and it exceeded the normal limit in one-third of the patients. Although NSE is a biomarker of neuronal injury, the clinical importance of this increase after AF ablation and its relationship with the left atrial diameter should be evaluated in a longitudinal study.